Neural Cell Adhesion Molecule Regulates Osteoblastic Differentiation Through Wnt/β-Catenin and PI3K-Akt Signaling Pathways in MC3T3-E1 Cells - Cheng, Bin-Feng; Feng, Xiao; Gao, Yao-Xin; Jian, Shao-Qin; Liu, Shi-Rao; Wang, Mian; Xie, Yun-Fei; Wang, Lei; Feng, Zhi-Wei; Yang, Hai-Jie (Frontiers in Endocrinology, 2021)
Neural cell adhesion molecule (NCAM) is involved in cell multi-directional differentiation, but its role in osteoblast differentiation is still poorly understood. In the present study, we investigated whether and how NCAM regulates osteoblastic differentiation. We found that NCAM silencing inhibited osteoblast differentiation in pre-osteoblastic MC3T3-E1 cells. The function of NCAM was further confirmed in NCAM-deficient mesenchymal stem cells (MSCs), which also had a phenotype with reduced osteoblastic potential. Moreover, NCAM silencing induced decrease of Wnt/β-catenin and Akt activation. The Wnt inhibitor blocked osteoblast differentiation, and the Wnt activator recovered osteoblast differentiation in NCAM-silenced MC3T3-E1 cells. We lastly demonstrated that osteoblast differentiation of MC3T3-E1 cells was inhibited by the PI3K-Akt inhibitor. In conclusion, these results demonstrate that NCAM silencing inhibited osteoblastic differentiation through inactivation of Wnt/β-catenin and PI3K-Akt signaling pathways.